Composition, squamation chronology and regeneration of the elasmoid scales of Oreochromis mossambicus (Perciformes) - PIUS, JOHNSON; PRAKASAM, V R (The Indian Journal of Animal Sciences, 2014)
The elasmoid scale of the teleost Oreochromis mossambiclls (Percifonnes) was studied to understand its composition, origin, development and regeneration. Analysis of organic constituents demonstrated the presence of higher percentage of protein compared to that of carbohydrates and lipids. Inorganic elemental cotr.position like K, Na, Ca, P, Cu, Pb, Mg, and Zn with reference to factors like size and habitat indicated that these factors influenced the distribution of rlements. Further, scales are suggested to function as a ’store house’ besides acting as a ’biological sink’ for detoxification. The study on squamation development revealed the time, sequence in the origin of scales and structures like radii, circuli, ctenii and tubulations. Observations on scale regeneration highlighted the role of epi-, hypo-and marginal scleroblasts and scale pocket lining in the development of scales from the dermis.